Toponymy of Village Names in Lhoknga District, Aceh Besar: An Anthropolinguistic Study - Cut Sukma Amelia; Denni Iskandar; Razali Razali (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Village names in Indonesia, especially in the Aceh region, hold meanings that are not only geographical, but also historical, social, and spiritual. This research raises the main issue related to the lack of in-depth studies on the toponymic meaning of village names in Lhoknga District, Aceh Besar, which has not been explored anthropolinguistically. The purpose of this research is to describe the origin and naming aspects of the village by exploring the cultural, historical, and linguistic meanings contained in the names. This research used a qualitative approach with an anthropolinguistic-based descriptive-analytical method, and data collection techniques were conducted through in-depth interviews, participatory observation, and archival and oral tradition documentation. The data were analyzed through a multidimensional approach that combines semantic, morphological, and social and cultural context aspects. The results show that village names such as Cot Bak U, Ujong Tanoh, and Lam Puuk not only function as location markers, but also represent value systems, historical narratives, and the community's spiritual relationship with its environment. Village naming has proven to be an important part of intangible cultural heritage that strengthens local identity and becomes a source of community knowledge. This research concludes that toponymy in Lhoknga reflects the close relationship between language, culture and history, and has strategic value in cultural preservation, education and community development.